2000
DOI: 10.1074/jbc.m004998200
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation Increases the α-Helical Content of the Histone Tails of the Nucleosome

Abstract: The nature of the structural changes induced by histone acetylation at the different levels of chromatin organization has been very elusive. At the histone level, it has been proposed on several occasions that acetylation may induce an ␣-helical conformation of their acetylated N-terminal domains (tails). In an attempt to provide experimental support for this hypothesis, we have purified and characterized the tail of histone H4 in its native and mono-, di-, tri-, and tetra-acetylated form. The circular dichroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
159
2
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(183 citation statements)
references
References 64 publications
20
159
2
2
Order By: Relevance
“…S2 and S3). Some of the qualitative trends of the conformational changes upon acetylation of LYS-16, observed from simulations, is consistent with the prior CD experiments, which reported steady increase in the alpha helical content of the H4 tails as a function of the number of added acetyl groups (35,36). Next, we probed the impact of the H4 tail acetylation on the DNA binding propensity.…”
supporting
confidence: 73%
“…S2 and S3). Some of the qualitative trends of the conformational changes upon acetylation of LYS-16, observed from simulations, is consistent with the prior CD experiments, which reported steady increase in the alpha helical content of the H4 tails as a function of the number of added acetyl groups (35,36). Next, we probed the impact of the H4 tail acetylation on the DNA binding propensity.…”
supporting
confidence: 73%
“…30 Indeed, studies have shown that a proportion of the histone tails adopt a helical formation, even when dissociated from nucleosomal DNA. 31 It is interesting to speculate that a similar conformation is produced by the H2A peptide or full-length protein when incubated with equimolar amounts of anionic bio-5 0 -AMP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evidence suggests that these domains also participate in protein-protein interactions between histones in the fully condensed chromatin fiber (3,7,16). Despite the perception of the tails as being "unstructured," biochemical and biophysical studies indicate they adopt defined structures and make specific interactions in chromatin (17)(18)(19)(20). The tail domains are not required for assembling or maintaining the structure of the nucleosome core and removal of the tails results in only marginal changes in the hydrodynamic shape, stability, and DNA wrapping within the nucleosome (21)(22)(23).…”
mentioning
confidence: 99%